Evaluating Treatment Outcome in an Interdisciplinary Pediatric Pain Service. (1st June 2000) - Bennett, Susan M; Chambers, Christine T; Bellows, Doria; Court, Colleen A; Huntsman, Elizabeth; Montgomery, Carolyne; Oberlander, Tim F; Sheriff, Michelle; Siden, Harold
Abstract : OBJECTIVE: To provide descriptive data evaluating outcome and treatment satisfaction among former pediatric patients and their parents seen in an interdisciplinary treatment program for complex pain syndromes. DESIGN: Retrospective telephone interview. SETTING: Pediatric academic health care centre. SUBJECTS AND METHODS: A semistructured interview designed for this study was administered by phone with 24 former patients (mean age 15.63 years) and parents, seen over the previous three years in the Complex Pain Consultation Service. Participants provided both qualitative and quantitative information about pre- and post-treatment levels of pain and functioning, achievement of treatment goals and satisfaction with the treatment program. RESULTS: Findings indicated significantly lower frequency and intensity of pain, as rated by patients, when current pain levels were compared with recalled pretreatment levels. As well, improvements were reported in strategies for managing pain and participation in regular activities of daily living.  Satisfaction with the team treatment was generally very high, and most felt that their goals were partially to completely met. Child and parent ratings of outcome and satisfaction were consistent. CONCLUSIONS: These descriptive data provide preliminary support for the application of an interdisciplinary model to treating disabling complex pain syndromes in children and youths.